IMPLEMENTASI PERATURAN BUPATI NOMOR 5 TAHUN 2015 TENTANG PENERAPAN PEMBELAJARAN MUATAN LOKAL DALAM BENTUK PESANTREN SEKOLAH DI SMPN 1 ASEMBAGUS - Agus Supriyadi; Djuwairiyah Djuwairiyah (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
SMP Negeri 1 Asembagus (State Junior High School 1 Asembagus) is the one of reference schools in implementing Situbondo Regent’s Regulation Number 5 in 2015 with coaching activities of reading and writing al-Qur’an in the form of Pesantren Sekolah (Concept of Islamic Boarding School in the School) so that the students can read al-Qur’an well and memorize Juz Amma at least 25 chapters correctly until these activities can give birth to the generation who have intellectual intelligence and noble character. The results showed that the Implementation of Regent’s Regulation Number 5 in 2015 at SMP Negeri 1 Asembagus (State Junior High School 1 Asembagus) by hold up Pesantren Sekolah (Concept of Islamic Boarding School in the School) activities. Supporting factors include intrinsic motivation of the students, Support from their family, and support from teaching staff of Tahfidul Qur’an Institution of Sukorejo Islamic Boarding School. Inhibiting factor include bad friends.